Contribution to the molecular phylogeny of Sciaridae (Diptera) with special attention to the genera Bradysia and Corynoptera - Arthofer, Wolfgang; Gollner, Andrea; Heller, Kai; Steiner, Florian M.; Schlick-Steiner, Birgit C.; Seeber, Julia (Zootaxa, 2021)
The systematics of the dipteran family Sciaridae is based mainly on morphological characters and has remained quite controversial. In this study, we used two mitochondrial DNA markers (CO1, 16S) and a nuclear one (28S) to take a glimpse into phylogenetic relationships of part of the North and Central European Sciaridae. A total of 91 species from 19 genera were analysed using Maximum Likelihood based phylogenetics (depending on the availability of valid sequences, 50–70 per gene). We strengthen the suggestion of the Chaetosciara group as an independent subfamily. Within the subfamily Megalosphyinae, two separate Bradysia clades were identified, suggesting a close relation between the genera Zygoneura, Austrosciara, and Scatopsciara. The genus Alpinosciara gen. n. is established to place the species of the former Corynoptera crassistylata group inside the subfamily Megalosphyinae. This new genus now includes 22 species.